1968
DOI: 10.1901/jeab.1968.11-489
|View full text |Cite
|
Sign up to set email alerts
|

ATTACK PRODUCED BY INTERMITTENT REINFORCEMENT OF A CONCURRENT OPERANT RESPONSE1

Abstract: Squirrel monkeys pressed a lever to produce food on several fixed-ratio schedules; they could also bite a rubber hose. Biting attack occurred during the postreinforcement pause and in early portions of the ratio response run. Also, biting attacks increased after transitions to higher values of the fixed-ratio requirement and in extinction. The results show that extinction-induced aggression effects occur in primates.Aggressive behavior is elicited by several different types of noxious stimulation (negative rei… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

13
90
1
2

Year Published

1969
1969
2019
2019

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 127 publications
(106 citation statements)
references
References 9 publications
13
90
1
2
Order By: Relevance
“…Rather, both birds would first orient themselves in frontofthe blue response key and then advance to the target bird. DISCUSSION The experiment supports the general observations of Hutehinson, Azrin, & Hunt (1968) and Gentry (1968) that fIXed-ratio food schedules generate concurrent aggressive behavior. The present data also support the finding of Hutehinson et al (1968) that attack behavior increased with increases in the fIXed-ratio response requirement.…”
supporting
confidence: 87%
See 1 more Smart Citation
“…Rather, both birds would first orient themselves in frontofthe blue response key and then advance to the target bird. DISCUSSION The experiment supports the general observations of Hutehinson, Azrin, & Hunt (1968) and Gentry (1968) that fIXed-ratio food schedules generate concurrent aggressive behavior. The present data also support the finding of Hutehinson et al (1968) that attack behavior increased with increases in the fIXed-ratio response requirement.…”
supporting
confidence: 87%
“…Recent experiments with pigeons (Azrin, Hutchinson, & Hake, 1966), rats (Thompson & Bloom, 1966), and monkeys (Hutchinson, Azrin, & Hunt, 1968) establish as an attack-inducing condition the transition from high reinforcement frequency to extinction. Furthermore, monkeys will bite a nearby rubber tube (Hutchinson et al, 1968), and pigeons will attack another live but restrained pigeon (Gentry, 1968) during early portions of an intermittent food schedule. The purpose of the present study was to (1) Each was maintained at 80% of its free-feeding body weight throughout the experiment.…”
mentioning
confidence: 99%
“…Hutchinson et al (1968) reported a similar shift in the distribution of aggressive biting to the postreinforcement pause and early stages of the ratio run during fixed-ratio responding in squirrel monkeys. The low incidence of attack responses during the final segment (40-60 sec) of the fixed interval appears to preclude the maintenance of aggressive behavior by superstitious reinforcement.…”
mentioning
confidence: 61%
“…Again, behavior that has been categorized as "aggressive" occurs most frequently during the pause (Gentry, 1968;Hutchinson, Azrin, & Hunt, 1968). Again, during the pause pigeons peck a key that terminates the stimulus normally accompanying the schedule, even when that action reduces the frequency of reinforcement (Appel, 1963;Azrin, 1961;Thompson, 1964Thompson, , 1965.…”
Section: Discussionmentioning
confidence: 99%